Anatomical Variants of the Sacroiliac Joint - Badr, Sammy; Khizindar, Huda; Boulil, Youssef; Abou Diwan, Ralph; Demondion, Xavier; Cotten, Anne (Seminars in Musculoskeletal Radiology, 2023)
Anatomical variants are frequently encountered when assessing the sacroiliac joints (SIJ) using magnetic resonance imaging. When not located in the weight-bearing part of the SIJ, variants associated with structural and edematous changes can be misinterpreted as sacroiliitis. Their correct identification is necessary to avoid radiologic pitfalls. This article reviews five SIJ variants involved in the dorsal ligamentous space (accessory SIJ, iliosacral complex, semicircular defect, bipartite iliac bony plate, and crescent iliac bony plate) and three SIJ variants involved in the cartilaginous part of the SIJ (posterior dysmorphic SIJ, isolated synostosis, and unfused ossification centers).
Keywords: anatomy; magnetic resonance imaging; sacroiliac joint; spondylarthritis; variant